2012
DOI: 10.1177/1352458512457843
|View full text |Cite
|
Sign up to set email alerts
|

Retinol levels are associated with magnetic resonance imaging outcomes in multiple sclerosis

Abstract: Serum retinol is inversely associated with simultaneous and subsequent MRI outcomes in RRMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 37 publications
1
34
3
Order By: Relevance
“…One recent study using the same technique for retinol assessment, found an inverse association between new lesion formation on MRI and vitamin A levels (Loken-Amsrud et al, 2012). We could not confirm an association between vitamin A and clinical disease activity in MS in our study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…One recent study using the same technique for retinol assessment, found an inverse association between new lesion formation on MRI and vitamin A levels (Loken-Amsrud et al, 2012). We could not confirm an association between vitamin A and clinical disease activity in MS in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…In the longitudinal study, the use of interferon-β did not influence our results. In studies by others on this topic conflicting results have been found: some found a synergistic effect of RA with interferon-β on T suppressor cell augmentation (Qu et al, 1998), others found the association between vitamin A and MRI outcomes to be non-significant during interferon-β use (Loken-Amsrud et al, 2012). We were unable to confirm any of this here.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…A reduction of retinol levels in MS patients compared with patients with noninflammatory neurologic diseases and with healthy controls has already been reported (32,33). Furthermore, a recent study described inverse association between increasing levels of s-retinol and MRI lesion activity in MS patients, finding s-retinol levels predicted MRI outcomes during subsequent months of follow-up (34). This is consistent with observations in different animal models.…”
Section: Discussionsupporting
confidence: 85%
“…19 One study on the other hand, designed to assess the association between vitamin D intake and MS risk, found no association between vitamin A intake, mainly from multivitamins, and MS risk. 20 The ORs of MS for RBP quintiles in the present study described a U-shaped pattern, which is not easily interpreted.…”
Section: Discussionmentioning
confidence: 99%